Catalytic CVD synthesis of boron nitride and carbon nanomaterials – synergies between experiment and theory. Issue 39 (29th August 2017) - McLean, Ben; Eveleens, Clothilde A.; Mitchell, Izaac; Webber, Grant B.; Page, Alister J.
Abstract : We present a perspective demonstrating the importance of synergy between experiment and theory for modern nanomaterial synthesis. Abstract : Low-dimensional carbon and boron nitride nanomaterials – hexagonal boron nitride, graphene, boron nitride nanotubes and carbon nanotubes – remain at the forefront of advanced materials research. Catalytic chemical vapour deposition has become an invaluable technique for reliably and cost-effectively synthesising these materials. In this review, we will emphasise how a synergy between experimental and theoretical methods has enhanced the understanding and optimisation of this synthetic technique. This review examines recent advances in the application of CVD to synthesising boron nitride and carbon nanomaterials and highlights where, in many cases, molecular simulations and quantum chemistry have provided key insights complementary to experimental investigation. This synergy is particularly prominent in the field of carbon nanotube and graphene CVD synthesis, and we propose here it will be the key to future advances in optimisation of CVD synthesis of boron nitride nanomaterials, boron nitride – carbon composite materials, and other nanomaterials generally.